2017
DOI: 10.5664/jcsm.6798
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Sleep Patterns and Problems by Race in a Clinical Sample of Black and White Preschoolers

Abstract: Study Objectives: Community-based research indicates that Black preschoolers tend to have more bedtime difficulties and are at higher risk for obstructive sleep apnea (OSA) compared to White preschoolers. This study examined differences in sleep patterns and problems by race among a clinical sample of Black and White preschoolers at an outpatient sleep clinic. Methods: Data were collected from electronic medical records for 125 children ages 2-5 years (mean = 3.37 years, 64.0% White, 36.0% Black; 59.2% male) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Exacerbating sleep health disparities, nonwhite children and those of lower SES may lack consistent access to health-care services. 73 Although more research is needed, some studies have found differences by race in practice patterns related to both general pediatric sleep services 74 and OSA diagnosis and treatment. 75 Innovative methods to promote sleep health and increase sleep problem identification and treatment are necessary to help reduce these disparities.…”
Section: Approaches To Addressing Pediatric Sleep Disparitiesmentioning
confidence: 99%
“…Exacerbating sleep health disparities, nonwhite children and those of lower SES may lack consistent access to health-care services. 73 Although more research is needed, some studies have found differences by race in practice patterns related to both general pediatric sleep services 74 and OSA diagnosis and treatment. 75 Innovative methods to promote sleep health and increase sleep problem identification and treatment are necessary to help reduce these disparities.…”
Section: Approaches To Addressing Pediatric Sleep Disparitiesmentioning
confidence: 99%